2014
DOI: 10.1002/ijop.12072
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and expectancy influences in placebo responding: The mediating role of attention

Abstract: Drawing upon research in perception and motivation, the current study proposes a motivation-attention model of placebo in which more motivated persons pay greater attention to placebo-related stimuli, directly influencing placebo response. We manipulated both motivation to respond to placebo and expectations of placebo response in a 2 × 2 design. Participants (N = 152) evaluated a series of placebo pheromones (slightly scented water) of potential romantic dates and made desirability ratings. Consistent with hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Previous experiences highly mediate expectancy in various ways: previous effective active treatments showed a higher likelihood to elicit placebo response [ 51 , 52 ], whereas ineffective results attenuate them [ 53 , 54 ], patients with more prolonged treatment exposure showed more significant placebo or nocebo effect [ 53 , 55 ]. Our results showed that 23% of the included studies investigated patients’ previous experiences, but the quasi-totality enrolled naive participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiences highly mediate expectancy in various ways: previous effective active treatments showed a higher likelihood to elicit placebo response [ 51 , 52 ], whereas ineffective results attenuate them [ 53 , 54 ], patients with more prolonged treatment exposure showed more significant placebo or nocebo effect [ 53 , 55 ]. Our results showed that 23% of the included studies investigated patients’ previous experiences, but the quasi-totality enrolled naive participants.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we did not take into account some EA items that may influence the placebo response and should be taken into consideration when planning a sham therapy. Particularly the operators’ empathy [ 88 ], the characteristics of the interaction between operators and participants (both verbal [ 51 ]) and nonverbal [ 31 ]) that can modify the patient perception of the therapy believability [ 44 ], including the eventual training of operator aimed at the style of rapport with the patient, and quality of patient-operator interaction [ 20 , 26 ] through a satisfaction questionnaire. Finally, although a protocol similar to Cerritelli et al [ 16 ] was followed, an a priori protocol for this methodological review has not been published.…”
Section: Discussionmentioning
confidence: 99%
“…They must sign a consent and therefore are motivated to help. This motivation to help makes participants more suggestible to the positive effects of any treatment and could be part of the difference between the present study and the other two Engebretsen et al studies [8]. Motivation could wane with infrequent contact as in the present study where subjects had only 3-5 physiotherapy (PT) sessions over the first weeks and then had no contact until follow-up by mail at six months.…”
Section: Study Volunteer Phenotypementioning
confidence: 71%
“…Among adults, patients who continued to take antidepressant medications as well as those who were switched to placebos had higher mean depression rating scale scores (47). However, more highly motivated patients showed greater responses to placebos as compared with less motivated patients, which highlights the importance of the patient's own level of motivation (48).…”
Section: Discussionmentioning
confidence: 99%